Remediação : mudanças no design de softwares evidenciadas através da análise da interface gráfica do aplicativo Waze - Londero, Eliene (2016)
This paper discuss the changes in software design after the smartphone emergence as a mobile communication device. To this end, were conducted interviews with local mobile application developers, specific literature review and analysis of the Waze's application design. This master´s thesis describes how the characteristics of the material support enable the creation of increasingly specific softwares and are crucial in the design of new media and mobile digital tools. When inserted in the new medium, changes are needed in the existing software, but there are also open possibilities for creating new apps for activities offered in this new development.